DETERMINAN LIKUIDITAS TERHADAP FINANCIAL PERFORMANCE DI INDUSTRI F&B YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ulfa Febriani (MANAJEMEN, 2025)
This study aims to evaluate the factors that influence liquidity on financial performance in the food and beverage industry sector listed on the Indonesia Stock Exchange. The sample selected includes 24 companies in the food and beverage sector listed on the Indonesia Stock Exchange during 2018 to 2023. The sampling procedure applied uses purposive sampling techniques, while the analysis method used panel data regression. The independent variables in this study was liquidity, leverage, company size, company age, board size, and board independence. The dependent variable was financial performance. The results indicate that board size, company size, company age, and leverage do not affect financial performance. Meanwhile, board independence and liquidity do affect firm performance. This study provides insight into the factors influencing firm value in the food and beverage sector, offers managerial implications and suggestions for future research, emphasizing the importance of sustainable growth in creating added value for stakeholders and enhancing industry competitiveness. This study also suggests exploring other variables that may influence financial results, offering a comprehensive understanding of industry dynamics.